2017
DOI: 10.1016/j.jid.2017.02.192
|View full text |Cite
|
Sign up to set email alerts
|

177 Surveillance adherence of patients after treatment of primary cutaneous melanoma

Abstract: Introduction: Male gender, age, fair skin, ultraviolet radiation and immunosuppression are known risk factors for BCC. However there is limited understanding of the impact of these risk factors with increasing frequency of BCC development. In this study, we sought to investigate the association of gender, age, BCC subtype, distribution and immunosuppressant use with increasing frequency of BCCs. Methods: We performed a retrospective cohort study of 3,392 BCCs biopsied in 1,419 patients between 2005 and 2015 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This may be due to a general increase in disease follow-up awareness, among patients with higher level education, medical insurance or the complement of adjuvant therapy, which were similar to previous reports. Reserva J, et al (Reserva et al 2017) found lacking health insurance were more likely to be poorly adherent to melanoma surveillance. Sanchez…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a general increase in disease follow-up awareness, among patients with higher level education, medical insurance or the complement of adjuvant therapy, which were similar to previous reports. Reserva J, et al (Reserva et al 2017) found lacking health insurance were more likely to be poorly adherent to melanoma surveillance. Sanchez…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that adherence to skin surveillance does decrease over time. In high-risk individuals, it is not until year 4 or 5 that the rates of adherence decrease significantly [55]. Considering the cost of genetic testing and the increasing public demand for such services, highquality research in this area is important and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Skin grafts or tissue transfers may be required if the main closure isn't possible. Patients with advanced melanoma get medical care as adjuvant therapy [29][30][31][32][33].…”
Section: Treatmentmentioning
confidence: 99%